Newnes radio and RF engineering pocket book - Winder, Steve; Carr, Joseph J.; Davies, John. (Oxford : Newnes, 2002)
New material in the third edition includes mobile base station antennas, operation of cellular networks, SAW filters and ceramic resonators, modulation for stereo FM broadcasts, ADPCM, and vocoders. *The essential data and information for modern radio engineering at your fingertips *Based on the practical knowhow of practicing engineers *Ideal for reference and revision.
Preface; Propagation of radio waves; The decibel scale; Transmission lines; Antennas; Resonant circuits; Oscillators; Piezo-electric devices; Bandwidth requirements and modulation; Frequency planning; Radio equipment; Microwave communication; Information privacy and encryption; Multiplexing; Speech digitization and synthesis; VHF and UHF mobile communication; Signalling; Mobile radio systems; Base station site management; Instrumentation; Batteries; Satellite communications; Connectors and interfaces; Broadcasting; Abbreviations and symbols; Miscellaneous data; Index.
Previous ed. published as: Newnes radio and RF engineer's book. / John Davies, Joseph C. Carr. 2000. originally published as: Newnes radio engineer's pocket book. / John Davies. 1994.
Includes bibliographical references and index.
Keywords: Radio -- Handbooks, manuals, etc; Electronic books